(untitled) (Revista Apotheke, 2020)
This essay presents part of the authorial photographic series entitled “From the basement to the attic” in which I seek to translate and create poetic daydreams and memories from references in the literature of Clarice Lispector and Gaston Bachelard. I explore the relationship between the house and the body as symbolisms, subjectivities and collectivities based on juxtapositions that weave art, psychoanalysis and phenomenology. The series in question was exposed in 2019 to various audiences, so that the educational actions proposed in that cultural space were also diverse. To show some photographic dialogues, I selected a specific group of elderly women and men who visited the exhibition and reported their memories and affections.